Drug holiday of high-dose denosumab and recovery from osteoclast inhibition using immunohistochemical investigation of 7 patients with medication-related osteonecrosis of the jaw undergoing segmental mandibulectomy - Shunsuke Sawada; Yuki Sakamoto; Mako Kirihigashi; Yuka Kojima (Elsevier, 2023)
Background/purpose: Denosumab is used to treat bone metastases from malignant tumors. Unlike bisphosphonates, denosumab is not deposited in the bone; thus, withdrawal for a relatively short period would help recovery from osteoclast suppression. This study investigated the relationship between drug holidays and recovery from osteoclast suppression. Materials and methods: Seven patients who received high-dose denosumab and underwent segmental mandibulectomy for medication-related osteonecrosis of the jaw were enrolled in this study. Osteoclast suppression (+) was defined as the absence of cathepsin K-positive cells or cathepsin K-positive mononuclear or small multinucleated cells observed on the bone surface of both mesial and distal specimens. When normal osteoclasts were found, osteoclast suppression was defined as (−); when both suppressed cathepsin K-positive cells and normal morphological osteoclasts were found, it was defined as (±). Results: Osteoclast suppression was: (+) in four patients, three without a drug holiday and one with a 9-month drug holiday; (±) in one patient with an 8-month drug holiday, and (−) in two patients with drug holidays for 13 and 20 months. Conclusion: These findings suggest that a long-term drug holiday, such as 12 months, is required for recovery from osteoclast suppression in patients with cancer receiving high-dose denosumab.